Why contexts matter for gender equal outcomes in research-based plant breeding: the case of maize in Nigeria - Yami, M.; Cavicchioli, M.; Cole, S. M.; Assfaw Wossen, T.; Abdoulaye, T. (Springer, 2024)
Maize is an important crop for food security and livelihood improvement in Nigeria and elsewhere in Africa. Maize varieties that enable farmers to increase their productivity and profitability, for example, can help them achieve these development outcomes. Contextual factors shape women’s and men’s preferences for specific maize traits and varieties, thus influencing varietal uptake and the contribution varieties make towards securing people’s livelihoods. Understanding contextual factors is paramount to pursuing gender equal outcomes within research-based maize breeding. We review literature on the demand for and access to improved maize varieties in Nigeria by using a framework that helps breeding programs become more gender-responsive and, thereby, enhance their impact via increased uptake. Findings show that attention towards the role of social norms in shaping the contexts where women and men maize farmers negotiate production-related decisions, form trait preferences, and access improved maize varieties has been limited within breeding programs, while ethnobotanical approaches are absent. To boost gender equal outcomes, maize breeding programs should identify the reasons motivating women’s and men’s varietal preferences and their different capacities to access improved varieties with the suited characteristics. To pursue this objective, gender-based Indigenous knowledge should be integrated since the first stages of varietal development.